2017
DOI: 10.1039/c7fd00094d
|View full text |Cite
|
Sign up to set email alerts
|

An integrated biorefinery concept for conversion of sugar beet pulp into value-added chemicals and pharmaceutical intermediates

Abstract: Over 8 million tonnes of sugar beet are grown annually in the UK. Sugar beet pulp (SBP) is the main by-product of sugar beet processing which is currently dried and sold as a low value animal feed. SBP is a rich source of carbohydrates, mainly in the form of cellulose and pectin, including d-glucose (Glu), l-arabinose (Ara) and d-galacturonic acid (GalAc). This work describes the technical feasibility of an integrated biorefinery concept for the fractionation of SBP and conversion of these monosaccharides into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 35 publications
0
28
0
Order By: Relevance
“…[8][9][10][11] or as substrates in chemical syntheses, e.g., for the production of fuels (bioethanol, methane, hydrogen), solvents, polymers, etc. [4,[12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11] or as substrates in chemical syntheses, e.g., for the production of fuels (bioethanol, methane, hydrogen), solvents, polymers, etc. [4,[12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Current work in our laboratory is investigating the utilisation of sugar beet pulp (SBP) as a renewable feedstock within the context of the AB Sugar Wissington biorefinery. Methods for the selective release of pectin from SBP have been established and for separation of the main monosaccharide components: l ‐arabinose and d ‐galacturonic acid . These have numerous industrial applications for production of biopolymers and hyperbranched polyesters and plasticisers .…”
Section: Introductionmentioning
confidence: 99%
“…Càrdenas‐Fernàndez et al reported the application of centrifugal partition chromatography (CPC) for simultaneous separation of all the pectin derived monosaccharides. CPC appears to be a promising separation technique for biorefinery applications, allowing a one‐step recovery of the two main monosaccharides present in SBP, i.e., Ara and GalA, with high yields and adequate purity from crude hydrolysate …”
Section: Methodsmentioning
confidence: 99%